Museo digital e interactivo para el municipio de Aipe - Huila (2021)
This document proposes to contribute to the research process on the municipality of Aipe. The most relevant aspects of its culture and tradition are addressed: festival, archaeological remains, traditions, and gastronomy of our Aipuna region. The different historical investigations already mentioned will be carried out for the municipality of Aipe, where the central nucleus of this analysis will begin from the foundation and origin of the main historical facts of the cultural pijao in the municipality of Aipe, also proposing a project that links new technological tools to show these historical events and events demarcated by the Pijao culture through three-dimensional elements (3d and 4d) to attract different digital scenarios at the departmental and national level. Likewise, the different expressions of the senses towards the public will be recognized without restricting them when carrying out one of the activities presented for the digital and interactive museum of the municipality of Aipe